Determination of Orobanche spp. distribution and Occurrence in North Gondar, Ethiopia - Mengistu, Anteneh Ademe; Ebabuye, Yohannes; Tilahune, Getachew; Gelaye, Mesganaw (ABC Journal of Advanced Research, 2017)
The survey was done on major pulse crop growing districts with the objective of assessing the distribution and occurrence of Orobanche spp. in the highlands of North Gondar. Representative Farmer’s fields from selected seven districts were assessed in every 5-10 km interval along the road ride to record the incidence, prevalence and severity of Orobanche spp. In all surveyed districts of N. Gondar Orobanche crenata was found with the highest prevalence and incidence of 85.71% and 10.71%, respectively on fields covered with Linseed. Among districts, the highest prevalence of 66.67% was recorded on both Chilga and Gonder zuria districts. In addition to this, a maximum severity of 3 out of 6 (i.e. majority of host plants infected with two shoots) was recorded only on two fields out of all fields surveyed of the seven districts. During the survey, it was found that Xanthium strumarium was its wild host. Finally, awareness creation and establishment of quarantine system should be done to minimize the dissemination of parasitic weed seed to other areas within the administrative zone and the region. Likewise, different management options should be developed in the future not only to minimize the yield loss due to Orobanche crenata but also to manage its wild hosts like Xanthium strumarium.